2010
DOI: 10.1016/j.cma.2010.06.018
|View full text |Cite
|
Sign up to set email alerts
|

On the existence of representative volumes for softening quasi-brittle materials – A failure zone averaging scheme

Abstract: a b s t r a c tThe concept of the representative volume element (RVE) for softening materials is revised in this contribution. It is demonstrated by means of numerical simulations that there exists a sample which is statistically representative for quasi-brittle materials with random microstructure like concrete. This finding is an important ingredient for homogenization-based multiscale modelling of softening materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
85
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 132 publications
(92 citation statements)
references
References 36 publications
2
85
0
2
Order By: Relevance
“…Note that the absence of a linear branch in the presented curves is due to the fact that the failure zone averaging should only be used after development of a failure band. Based on this observation plus a statistical analysis presented in [21], the authors have confirmed the existence of an RVE for quasi-brittle materials with random heterogeneous microstructure that exhibit localized failure with a continuum damage model. …”
Section: Failure Zone Averaging Techniquementioning
confidence: 62%
See 4 more Smart Citations
“…Note that the absence of a linear branch in the presented curves is due to the fact that the failure zone averaging should only be used after development of a failure band. Based on this observation plus a statistical analysis presented in [21], the authors have confirmed the existence of an RVE for quasi-brittle materials with random heterogeneous microstructure that exhibit localized failure with a continuum damage model. …”
Section: Failure Zone Averaging Techniquementioning
confidence: 62%
“…In [21], the existence of an RVE for quasi-brittle materials (under tensile loading) with random complex heterogeneous microstructure exhibiting diffusive damage has been confirmed based upon a special averaging scheme, the failure zone averaging scheme, which filters out the linear contribution of the micro sample.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations